2018
DOI: 10.1080/02763869.2018.1404386
|View full text |Cite
|
Sign up to set email alerts
|

DigitalHub: A Repository Focused on the Future

Abstract: The DigitalHub scholarly repository was developed and launched at the Galter Health Sciences Library for the Feinberg School of Medicine and the greater Northwestern Medicine community. The repository was designed to allow scholars the ability to create, share, and preserve a range of citable digital outputs. This article traces the evolution of DigitalHub's development and engagement activities, highlighting project challenges, innovations, success stories, and the team-based approach that was employed to suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The results of this study provide valuable information about the availability of, characteristics of, and future plans for IRs in medical schools and academic health centers. This study addresses a gap in the professional literature by gathering granular and up-to-date information from AAHSL member libraries about their IRs, allowing us to look at trends and acquire a generalized view beyond individual cases and pilot studies [24], website and directory surveys [5, 6], and brief availability statistics that have been compiled by AAHSL [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study provide valuable information about the availability of, characteristics of, and future plans for IRs in medical schools and academic health centers. This study addresses a gap in the professional literature by gathering granular and up-to-date information from AAHSL member libraries about their IRs, allowing us to look at trends and acquire a generalized view beyond individual cases and pilot studies [24], website and directory surveys [5, 6], and brief availability statistics that have been compiled by AAHSL [11].…”
Section: Discussionmentioning
confidence: 99%
“…Fay et al described the process for setting up and populating an IR for the large Aurora Health Care system in Wisconsin [3]. Also, Ilik et al reported on the development and launch of a next-generation repository for the nontraditional scholarly outputs of Northwestern Medicine [4].…”
Section: Introductionmentioning
confidence: 99%